1999
DOI: 10.1136/ard.58.2.72
|View full text |Cite
|
Sign up to set email alerts
|

The shape of the distal femur: a palaeopathological comparison of eburnated and non-eburnated femora

Abstract: Objectives-To determine the diVerence in shape of the distal femur, viewed axially in two dimensions, between eburnated and non-eburnated femora. Methods-A comparison of 52 noneburnated and 16 eburnated femora drawn from a large archeological skeletal population. Eburnation was taken to indicate late stage osteoarthritis. Shape variability, based on landmarks, was quantified using a principal components analysis after a Procrustes alignment. Results-A statistically significant diVerence was found between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 25 publications
(16 reference statements)
1
29
2
Order By: Relevance
“…These authors found that there was a difference in the shape of femora with and without eburnation, but they could not conclude that any of the observed differences in shape are risk factors for the development of osteoarthritis in human knee joints. 21 The cause of fragmented coronoid process in Rottweilers cannot be explained by data of the study reported here. Our study examined only a single component of the elbow joint, the articular plane defined by the ulnar trochlear notch.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…These authors found that there was a difference in the shape of femora with and without eburnation, but they could not conclude that any of the observed differences in shape are risk factors for the development of osteoarthritis in human knee joints. 21 The cause of fragmented coronoid process in Rottweilers cannot be explained by data of the study reported here. Our study examined only a single component of the elbow joint, the articular plane defined by the ulnar trochlear notch.…”
Section: Discussioncontrasting
confidence: 53%
“…[19][20][21] Bullough et al 20 stated that there is a necessary physiologic incongruity in diarthrodial joints that facilitates the even distribution of load across the joint surfaces, maximizes joint stability, and maintains the nutrition of articular cartilage by facilitating the movement of synovial fluid into the articular cartilage. Age-related remodeling of joints results in altered load distribution with subsequent articular cartilage degeneration and development of osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…The field of FDA is quite new and there is still a lot of work to be done, but several applications in different fields have been developed in recent years. Examples include such applications as the bone shape analysis (Shepstone et al, 1999), the study of human growth , the motor control of speech (Lucero and Koening, 2000), handwriting movements (Ramsay, 2000) or the analysis of the fingers' pinch force . Registration is a very interesting tool for functional data analysis and it provides a local nonlinear normalization of time functions.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 68 outlines were studied, which correspond to 52 non-eburnated and 16 eburnated femora. They considered 12 landmarks (see Shepstone et al (1999) for details about data and identification and construction of these landmarks) 1 .…”
Section: Shapes Through Three Approachesmentioning
confidence: 99%